2017
DOI: 10.1186/s12955-017-0621-0
|View full text |Cite
|
Sign up to set email alerts
|

Using patient values and preferences to inform the importance of health outcomes in practice guideline development following the GRADE approach

Abstract: BackgroundThere are diverse opinions and confusion about defining and including patient values and preferences (i.e. the importance people place on the health outcomes) in the guideline development processes. This article aims to provide an overview of a process for systematically incorporating values and preferences in guideline development.MethodsIn 2013 and 2014, we followed the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach to adopt, adapt and develop 226 recommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
92
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 40 publications
1
92
0
2
Order By: Relevance
“…Shared decision-making processes can reconcile individual and population perspectives for cancer screening by addressing the individual acceptability of tests in the context of HCP values and evidence-informed recommendations (Grad et al, 2017; Lang et al, 2018). Therefore, a shared decision-making framework can guide processes to elicit preferences in cancer screening, aligning with person-centered and evidence-informed practice (Hoffmann et al, 2014; Zhang et al, 2017). To support preference elicitation and shared decision making in cervical cancer screening, we need to know how stakeholders, including women eligible for screening and HCPs, perceive the decision.…”
mentioning
confidence: 99%
“…Shared decision-making processes can reconcile individual and population perspectives for cancer screening by addressing the individual acceptability of tests in the context of HCP values and evidence-informed recommendations (Grad et al, 2017; Lang et al, 2018). Therefore, a shared decision-making framework can guide processes to elicit preferences in cancer screening, aligning with person-centered and evidence-informed practice (Hoffmann et al, 2014; Zhang et al, 2017). To support preference elicitation and shared decision making in cervical cancer screening, we need to know how stakeholders, including women eligible for screening and HCPs, perceive the decision.…”
mentioning
confidence: 99%
“…Some researchers have suggested that valid, acceptable preference‐elicitation tools might facilitate the integration of women's preferences into cervical cancer screening clinical practice and guidelines, because the tool promotes values‐based decision‐making in an evidence‐informed way. “Cervical cancer screening—it's your choice” explicitly acknowledges that women face a decision to undergo cervical cancer screening, and if they choose to participate, they may choose different options because they value the risks and benefits differently.…”
Section: Discussionmentioning
confidence: 99%
“…Among Canadian jurisdictions, cervical cancer screening recommendations do not explicitly refer to women's preferences for screening despite the potential importance of different values and preferences. Specifically, guidelines do not allude to population estimates of preferences, and there are no recommendations for providers to elicit preferences from women at the point‐of‐care . To be consistent with the person‐centred, evidence‐informed vision of high‐quality health care systems, cervical cancer screening guidelines and practice would ideally integrate women's informed, values‐based preferences.…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…The results from this study indicate that individuals reflect on many personal values when considering issues related to precision medicine. An understanding of these values is important to the field as patient values have been tied to effective implementation of evidence‐based medicine and improved healthcare service engagement (Sackett et al ; Zhang et al ). We asked participants about their values related to genetic testing, one of the most recognizable precision medicine services.…”
Section: Discussionmentioning
confidence: 99%